Analisis Hambatan dan Kesulitan Belajar Siswa Kelas X MAN 3 MEDAN dalam Materi Eksponen dan Logaritma - Kairuddin Kairuddin; Fithrah Amalia Sirait; Devita Syahputri; Dinda Rizky; Nabila Nasution; Syeila Fatiha; Siti Aisyah Lubis (Lembaga Pengembangan Kinerja Dosen, 2025)
Using Newman's Error Analysis (NEA) as a framework, this study will examine the many ways in which MAN 3 Medan students blunder while answering problems involving logarithms and exponentials. A total of thirty-one MIPA class X students served as subjects for this qualitative descriptive study. Essay tests, interviews with math instructors, and records of student work all contributed to the data set. Data analysis involves reducing, presenting, and making conclusions while triangulating sources to ensure the data is legitimate. According to the research, the two most common points of mistake are when people are trying to grasp the issue and when they are trying to convert it. This is because pupils have a hard time grasping the characteristics and fundamental ideas of logarithms and have a habit of rote memorization rather than critical thinking. Other factors that also affect include the lack of utilization of learning media and low student learning motivation. After being given discussion-based learning and interactive media, the post-test results showed an increase in comprehension and a decrease in conceptual errors. This research recommends that teachers should emphasize student-centered learning by strengthening basic concepts and implementing contextual problem-solving strategies.